Akuntabilitas Pengelolaan Keuangan Panti Asuhan Rabbani di Maros - Rasyidah Nadir; Tawakkal Tawakkal; Hasyim M.; Dewanti Eka Pratiwi (AKUNSIKA: Jurnal Akuntansi dan Keuangan, 2022)
Financial management accountability is an instrument of accountability for the use of organizational funds. Governance in preparing financial statements is important for orphanages. The purpose of this study is to prepare financial reports based on Statement of Financial Accounting Standards (PSAK) Number 45. The data analysis technique used is quantitative descriptive analysis. Quantitative descriptive analysis is an analytical method by processing the available data in the form of numbers as a guide for preparing financial reports at the Rabbani Orphanage. The results of the study indicate that the financial statements that have been prepared based on PSAK No. 45 describes the net assets owned as of January 1, 2020, valued at Rp 749,652,000. The net asset component consists of unrestricted net assets of Rp 59,290,000 and permanently restricted net assets of Rp 691,022,000. an increase in unrestricted net assets by Rp 80,613,250. Then, in the statement of financial position, net assets are free of Rp 139,903,250 and Rp 691,022,000 for permanently bound net assets.